Pedestrian Infrastructure Quality of Service In Urban Neighborhood: A Case Study in Wangsa Maju, Kuala Lumpur, Malaysia: A Case Study in Wangsa Maju, Kuala Lumpur, Malaysia - Ida Shaheera Bakhtiar; Safizahanin Mokhtar; Muhammad Zaly Shah Hussein (Tecno Scientifica Publishing, 2022)
The effectiveness of security and accessibility to all facilities supplied in the neighborhood area was evaluated using the Pedestrian Infrastructure Quality of Service methodology. The method is known as a